Duality and ontology - Le Bihan, B; Read, J (John Wiley and Sons, Inc., 2018)
A “duality” is a formal mapping between the spaces of solutions of two empirically equivalent theories. In recent times, dualities have been found to be pervasive in string theory and quantum field theory. Naïvely interpreted, duality‐related theories appear to make very different ontological claims about the world—differing in, for example, spacetime structure, fundamental ontology, and mereological structure. In light of this, duality‐related theories raise questions familiar from discussions of underdetermination in the philosophy of science: in the presence of dual theories, what is one to say about the ontology of the world? In this paper, we undertake a comprehensive and nontechnical survey of the landscape of possible ontological interpretations of duality‐related theories. We provide a significantly enriched and clarified taxonomy of options—several of which are novel to the literature.